Adverse effects of paracetamol - Konopelko, Michał; Szafraniec, Aneta; Porada, Dominik; Pucułek, Małgorzata; Przybylska, Daria (Journal of Education, Health and Sport, 2017)
Admission. Paracetamol (acetaminophen) is one of the most popular medicinal substances in the world, characterized by analgesic and antipyretic properties. This pharmacy is issued without a prescription and can be purchased not only in pharmacies. Easy accessibility and lack of full control over its sales lead to the abuse of paracetamol, creating a risk of side effects. Purpose of work. The aim of the study is to present adverse reactions in paracetamol treatment, with particular emphasis on the risk of hepatotoxicity. Paracetamol (up to 4g / day) may cause nausea, diarrhea, skin lesions and haematological disorders during therapy. The most serious side effect of paracetamol is, however, a hepatotoxic effect that can cause acute liver failure leading to total hepatic necrosis. If paracetamol poisoning is observed (at doses above 8 g / day), antidote treatment should be considered: N-acetylcysteine and liver transplantation. Unfortunately, many times patients die. Summary. The social conviction of low harm of paracetamol and the high availability of preparations containing this substance make the side effects an important aspect of therapy with this drug. Acute poisoning with paracetamol, which often results in liver failure, is an important problem for modern toxicology.